Copper-catalyzed synthesis of oxime ethers from iminoxy radical (CN–O) and maleimides via radical addition. Issue 43 (24th October 2019) - Han, Ziwei; Shen, Subo; Zheng, Feng; Hu, Han; Zhang, Jianmin; Zhu, Shizheng
Graphical abstract: Highlights: An efficient Cu(II)-catalyzed radical addition reaction of ketoximes with N -substituted maleimides. Synthesis of O -( N -substituted-2, 5-dicarbonyl pyrrolidine)-oxime ether products in moderate to good yields. The evidence of oxime radical confirmed by EPR spectroscopy. The radical addition reaction mechanism indicated by variable-temperature 1 H NMR. Abstract: An efficient Cu(II)-catalyzed radical addition of maleimides has been achieved. The identified copper catalyst enables the formation of oxime radicals (N–O) by cleaving the O–H bond in ketoximes, followed by the radical addition to N -substituted maleimides. The oxime radicals (N–O) were detected and confirmed by EPR spectroscopy and variable-temperature 1 H NMR. The simple one-pot reaction realizes the facile preparation of a variety of oxime ether adduct products in moderate to good yields.